A Perspective on Implementation of Technology-Driven Exergames for Adults as Telerehabilitation Services - Meulenberg, Cécil J. W.; de Bruin, Eling D.; Marusic, Uros (Frontiers in Psychology, 2022)
A major concern of public health authorities is to also encourage adults to be exposed to enriched environments (sensory and cognitive-motor activity) during the pandemic lockdown, as was recently the case worldwide during the COVID-19 outbreak. Games for adults that require physical activity, known as exergames, offer opportunities here. Recent developments, optimization, and minimizations in wearable technology have produced wireless headsets and sensors that allow for unrestricted whole-body movement. This makes the virtual experience more immersive and provides the opportunity for greater engagement than traditional exercise. Currently, extended reality (XR) serves as an umbrella term for current immersive technologies as well as future realities that enhance the experience with features that produce new controllable environments. Technology-enhanced exergames challenge the adult user and modify the experience by increasing sensory stimulation and creating an environment where virtual and real elements interact. Exergame therapy can potentially create new environments and visualizations that may be more ecologically-valid. To more optimally serve and challenge adults both physically and cognitively over time in future lockdowns, there is a need to provide long-term remote training and feedback, particularly related to activities of daily living that create opportunities for effective and lasting rehabilitation for elderly and sufferers from chronic non-communicable diseases (CNDs). The aim of the current perspective review is to envision the remote training and monitoring of physical and cognitive aspects for adults with limted mobility (due to disability, disease or age), through the implementation of concurrent telehealth and exergame features using XR and wireless sensor technologies.